C-MET inhibition: novel treatment for sporadic and MEN1-associated GEP NETs. (August 2020) - Lee, Maya Elena; Tepede, Aisha Aderayo; Mandl, Adel; Weinstein, Lee Scott; del Rivero, Jaydira; Agarwal, Sunita K; Blau, Jenny E
Abstract : Gastroenteropancreatic neuroendocrine tumors (GEP NETs) comprise a heterogenous and diverse group of neoplasms arising from a common neuroendocrine cell origin. The majority of these tumors occur sporadically while ~20% manifest within the context of hereditary syndromes. Germline MEN1 mutations cause a syndrome with an increased susceptibility to multifocal primary GEP NETs. In addition, somatic MEN1 mutations also occur in these sporadic lesions. MEN1 alterations are the most frequent somatic mutation found in pancreatic neuroendocrine tumors. In this review, we explore the implication of the loss of the MEN1 -encoded protein menin as a key pathogenic driver in subsets of GEP NETs with downstream consequences including upregulation of the oncogenic receptor c-MET (hepatocyte growth factor receptor). Furthermore, the review will summarize the data related to the clinical presentation, therapeutic standards, and outcomes of these tumors in both sporadic and germline MEN1 mutation-associated contexts. Finally, we present the data on c-MET expression in GEP NETs, clinical trials using c-MET inhibitors and provide an overview of the molecular mechanisms by which c-MET inhibition in these lesions represents a potential precision-medicine targeted approach.